Prunus Mahaleb Fruit Extract Prevents Chemically Induced Colitis and Enhances Mitochondrial Oxidative Metabolism via the Activation of the Nrf2 Pathway. Issue 22 (22nd August 2019) - Ferramosca, Alessandra; Treppiccione, Lucia; Di Giacomo, Mariangela; Aufiero, Vera Rotondi; Mazzarella, Giuseppe; Maurano, Francesco; Gerardi, Carmela; Rossi, Mauro; Zara, Vincenzo; Mita, Giovanni; Bergamo, Paolo
Abstract : Scope: Polyphenols exhibit their antioxidant activity downstream the activation of the nuclear factor erythroid 2‐related factor 2 pathway (Nrf2), but the connection between lipid metabolism and the Nrf2 pathway is still unknown. Flavonoid‐rich concentrated extract from Prunus mahaleb (mahaleb concentrated fruit extract; MCFE) may act on oxido‐reductive homeostasis and hepatic lipid metabolism via Nrf2. Methods & Results: MCFE ability to enhance the activity of Nrf2‐mediated antioxidant/detoxifying enzymes is investigated in liver and colon of BALB/c mice. After a 4‐week supplementation, macroscopic, histological, and biochemical signs of colitis are examined in mouse colon pulsed with 5% (w/v) dextran sodium sulfate (DSS). Untreated or DSS‐supplemented mice are used as negative or positive control. MCFE effect on liver lipid metabolism and its possible link with the Nrf2 pathway is investigated. MCFE intake increases antioxidant defenses in mice colon and its pretreatment blunts pathological signs of colitis, as compared to positive control. In the liver, the increase in antioxidant defenses is associated with enhanced oxidative metabolism and with higher levels of peroxisome proliferator‐activated receptor gamma coactivator 1‐alpha (PGC‐1α) and of hemeoxygenase‐1 (HO‐1), in comparison with negative controls. Conclusion: Cytoprotective and hypolipidemic effect produced by MCFE intake results, at least in part, by the activation of the Nrf2 pathway. Abstract : Dietary supplementation with polyphenol‐rich extract of Mahaleb fruit (MCFE), improves oxidoreductive homeostasis of mouse colonic tissue via the activation the Nuclear erythroid related factor2 (Nrf2) pathway and prevent chemically‐induced colitis. Moreover, accordingly to the recognized crosstalk between Nrf2 and lipid metabolism, improved Nrf2‐mediated defenses in liver is accompanied by the decline of fat synthesis and the increase of β‐oxidation.